PENGARUH PENERAPAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) TERHADAP LINGKUNGAN BELAJAR KOLABORATIF PADA MATA PELAJARAN IPA KELAS VIII SMPIT ADZKIA PADANG - Azikra Chasiaturahmi; Meldi Ade Kurnia Yusri; Alkadri Masnur; Elsa Masriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Twenty-first century learning requires students to develop various competencies, one of which is collaboration, as an essential skill to support meaningful learning. However, based on observations conducted at SMPIT Adzkia Padang, students' collaboration and participation in science learning were not yet optimal, resulting in a collaborative learning environment that had not been fully established. Therefore, this study aimed to determine the effect of implementing the Contextual Teaching and Learning (CTL) model on improving the collaborative learning environment of eighth-grade students at SMPIT Adzkia Padang. This study employed a quantitative approach using a quasi-experimental method with a Posttest Only Control Group Design. The sample consisted of Class VIII Cordova A (33 students) as the experimental group and Class VIII Cordova B (32 students) as the control group, selected through purposive sampling. Data were collected using a valid and reliable collaborative learning environment questionnaire and analyzed using descriptive and inferential statistics, including the Shapiro–Wilk normality test, Levene's Test for homogeneity, and the Independent Samples t-test. The findings revealed that students taught using the Contextual Teaching and Learning (CTL) model demonstrated a higher collaborative learning environment than those taught using the Problem Based Learning (PBL) model. The hypothesis testing result showed a significance value of Sig. (2-tailed) < 0.001, indicating that the implementation of the CTL model had a significant effect on improving students' collaborative learning environment. Therefore, the CTL model can be considered an effective alternative learning model for fostering a more collaborative and meaningful science learning process.